Monitoring populations of the ham mite, Tyrophagus putrescentiae (Schrank) (Acari: Acaridae): research on traps, orientation behavior, and sampling techniques - Amoah, Barbara Amoh (Kansas State University, 2016)
The phase-out of methyl bromide production, the most effective fumigant for the control of the ham mite, Tyrophagus putrescentiae (Schrank) (Acari: Acaridae), on dry-cured ham has necessitated the search for other management methods. The foundation of a successful management program is an effective monitoring program that provides information on pest presence and abundance over time and space to help in making management decisions. By using the standard trap made from disposable Petri dishes and a dog food-based bait, mite activity was monitored weekly in five dry-cured ham aging rooms from three commercial processing facilities from June 2012 to September 2013. Results indicated that mite numbers in traps in facilities typically had a pattern of sharp decline after fumigation, followed by a steady increase until the next fumigation. Average trap captures varied due to trap location, indicating that traps could be used to identify locations where mite infestation of hams may be more likely to occur. Experiments were also conducted in 6 m x 3 m climate-controlled rooms to determine the effects of some physical factors on trap capture. Factors such as trap design, trap location, trap distance, duration of trapping, and light conditions had significant effects on mite capture. Mites also responded differently to light emitting diodes of different wavelengths, either as a component of the standard trap or as a stand-alone stimulus to orientation. To determine the relationship between trap capture and mite density, experiments were carried out in the climate-controlled rooms. Mite density was varied but trap number remained constant for all mite densities. There was strong positive correlation between trap capture and mite density. In simulated ham aging rooms, the distribution of mites on hams was determined and different sampling techniques such as vacuum sampling, trapping, rack sampling, ham sampling and absolute mite counts from whole hams were compared and correlated. Results showed weak or moderate correlations between sampling techniques in pairwise comparisons. Two sampling plans were developed to determine the number of samples required to estimate mite density on ham with respect to fixed precision levels or to an action threshold for making pest management decisions. Findings reported here can help in the optimization of trapping and sampling of ham mite populations to help in the development of efficient, cost-effective tools for pest management decisions incorporated with alternatives to methyl bromide.
Keywords: Tyrophagus putrescentiae; Stored products; Dry-cured ham; Behavior; Trapping efficiency; Sampling and sampling plans